2012
DOI: 10.1037/a0023155
|View full text |Cite
|
Sign up to set email alerts
|

Religious coping, stress, and depressive symptoms among adolescents: A prospective study.

Abstract: This study examined prospective associations between religious coping, stress, and depressive symptoms in a community sample of 111 adolescents (80 female). We hypothesized that religious coping would moderate the relationship between stress and depressive symptoms, with negative religious coping exacerbating the effects of stress on depressive symptoms and positive religious coping buffering the effects of stress on depressive symptoms. We further expected that the moderating effects of religious coping on ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 45 publications
11
60
2
4
Order By: Relevance
“…Epidemiological studies indicate people frequently rely on religion to cope with life stresses, with meta-analyses demonstrating positive impacts of religious coping on wellbeing (Ano & Vasconcelles, 2005;Harrison, Koenig, Hays, Eme-Akwari, & Pargament, 2001). Additionally, a smaller number of studies has found religious coping to moderate the relationship between stress and wellbeing, providing support for the buffering hypothesis (Aydin, Fischer, & Frey, 2010;Carpenter, Laney, & Mezulis, 2012;Fernandez & Loukas, 2014;Tix & Frazier, 1998). These findings elucidate the two mechanisms by which coping can affect adaptation outcomes (Ensel & Lin, 1991).…”
Section: The Role Of Religion In Coping With Stressmentioning
confidence: 82%
“…Epidemiological studies indicate people frequently rely on religion to cope with life stresses, with meta-analyses demonstrating positive impacts of religious coping on wellbeing (Ano & Vasconcelles, 2005;Harrison, Koenig, Hays, Eme-Akwari, & Pargament, 2001). Additionally, a smaller number of studies has found religious coping to moderate the relationship between stress and wellbeing, providing support for the buffering hypothesis (Aydin, Fischer, & Frey, 2010;Carpenter, Laney, & Mezulis, 2012;Fernandez & Loukas, 2014;Tix & Frazier, 1998). These findings elucidate the two mechanisms by which coping can affect adaptation outcomes (Ensel & Lin, 1991).…”
Section: The Role Of Religion In Coping With Stressmentioning
confidence: 82%
“…Subsequent studies have confirmed the association of positive coping with higher levels of reported well-being, including better quality of life and mental health in patients with advanced cancer. [23][24][25][26] Nine of 13 of Melissa's categories correspond to Pargament and colleagues' positive coping categories (Table 2). Negative coping methods were limited to 3 prayers: prayer 11 expressing loneliness, prayer 14 expressing shock and dismay at metastatic disease, and prayer 15 expressing concern with conflict with her boyfriend.…”
Section: Discussionmentioning
confidence: 96%
“…Epidemiological studies indicate people frequently rely on religion to cope with life stresses, with meta-analyses demonstrating positive impacts of religious coping on wellbeing (Ano & Vasconcelles, 2005;Harrison, Koenig, Hays, Eme-Akwari, & Pargament, 2001). Additionally, a smaller number of studies has found religious coping to moderate the relationship between stress and wellbeing, providing support for the buffering hypothesis (Aydin, Fischer, & Frey, 2010;Carpenter, Laney, & Mezulis, 2012;Fernandez & Loukas, 2014;Tix & Frazier, 1998). These findings elucidate the two mechanisms by which coping can affect adaptation outcomes (Ensel & Lin, 1991).…”
Section: The Role Of Religion In Coping With Stressmentioning
confidence: 92%